Lost boy found / [compact disc, unabridged] - Alexander, Kirsten (Blackstone Publishing, 2020)
In 1913, on a summer's day at Half Moon Lake, Louisiana, four-year-old Sonny Davenport walks into the woods and never returns. The boy's mysterious disappearance from the family's lake house makes front-page news in their home town. His parents are wealthy and influential, and will do anything to find their son. For two years, they search, struggling not to give in to despair. Then, when all hope seems lost, the boy is found in the company of a tramp. But is he truly Sonny Davenport?